Environmental impacts in the Cabedelo Municipal Natural Park – State of Paraíba, Brazil. - Pereira de Lima, Wendel (2021)
In geography, the study of conservation units is essential for understanding the relationships between society and nature.  The present work aims to analyze human activities and the environmental impacts identified in and around the Cabedelo Municipal Natural Park, which houses an important natural heritage of restingas, located in the urban area of ​​the municipality of Cabedelo, state of Paraíba, in Northeastern Brazil.  According to geosystemic methodology, the methodological procedures adopted consisted of bibliographic analysis, documentary research in public agencies, field work for the generation of photographic records, on-site observations and the application of questionnaires to residents.  The site has been the target of several impactful actions arising from anthropogenic activities and the lack of adequate management by municipal authorities, which has reinforced the perception on the local population that the park’s situation is worsening.